Select Epigrams from the Greek Anthology - Mackail, J. W. (John William), 1859-1945 (Salt Lake City, UT : Project Gutenberg, 2000)
"Select Epigrams from the Greek Anthology" by J. W. Mackail is a collection of poetic epigrams first published in the late 19th century. The anthology presents a curated selection of Greek epigrams, both in their original Greek and in English translation, aiming to showcase the finest examples of this genre from ancient to Byzantine poetry. The work serves not only as a literary collection but also provides readers with insights into various aspects of life, love, and art as expressed through concise, poignant verse. At the start of this anthology, the preface outlines the editor's dedication to collecting epigrams of the highest quality, recognizing the subjectivity involved in their selection. The introduction provides a thorough exploration of the origins and definitions of epigrams, tracing their evolution from simple inscriptions to multifaceted poetic expressions. Mackail emphasizes their unique qualities, such as brevity and clarity, while also delving into the historical development of epigrammatic poetry throughout Greek history, from classical times through the Byzantine era. This opening portion lays a foundation for understanding the significance and beauty of the epigrams to follow, framing them within a rich literary tradition. (This is an automatically generated summary.)
Uniform title: Greek anthology. Selections
Release date is 2000-10-01
Keywords: Epigrams, Greek; Greek poetry -- Translations into English